Empowering of UMKM Kremes Rahayu and Nineung Crackers in The Development of Dayeuhluhur Village - Subagja, Andreas; Karmila, Intan; Uswah, Fauziyatun Nurul; Syanissa, Meilani; Anggraeni, Dhita Mia; Romadhona, Rifqi; Putra, Reza Cahaya; Pabyana, Randi; Fauzi, Rizki Muhamad; Sutarya, Hana Hemalina (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Fundamental problems in the development of micro, small and medium enterprises (UMKM) are related to capital, business management, financial management and marketing of the products produced. Most UMKM, especially micro-scale businesses in the home industry are still experiencing problems in obtaining and increasing sales continuously because of product marketing that relies on conventional marketing methods, such as sales through exhibitions or direct sales. Kremes and cracker UMKM products located in Dusun Dayeuhluhur were developed through product branding with the aim of providing a unique identity for products in the market share. This product branding includes creating product logos and marketing them online. The results can be in the form of increased online sales and the intended product can be known by the wider community